PEMBUATAN ARANG AKTIF DARI BATOK BIJI KLUAK SEBAGAI ADSORBEN AIR SUMUR YANG TERCEMAR - Fatimah, Sitti; Iswadi, Iswadi; Said L, Muh (JFT: Jurnal Fisika dan Terapannya, 2018)
This research aims to determine the mineral content of activated charcoal made from kluwak seed shell, the quality of activated charcoal made from kluwak seed shell, and the absorption capacity of kluwak seed shell charcoal as adsorbent of polluted well water after testing. From the results of XRF analysis, it can be seen that there are still several types of impurities in activated carbon shells of kluwak seeds. It can be said that the activated carbon obtained is not yet fully pure activated carbon because pure activated carbon only contains 100% carbon. Where the quality of activated charcoal made from kluwak seed shells meets the requirements of SNI-06-3730-1995 in terms of water content and ash content. And the absorption capacity of Kluwak sage shell charcoal as an adsorbent of contaminated well water after testing, namely the gravel, activated carbon, and silica sand have met the clean water eligibility standards when viewed from turbidity and color while in the gravel filter layer, silica sand, carbon and in the silica sand filter, activated carbon, gravel have not met the eligibility requirements for clean water because of the high turbidity and the solid color.